HUBUNGAN POLA MAKAN, AKTIVITAS FISIK, DAN PENGETAHUAN GIZI SEIMBANG DENGAN STATUS GIZI PADA REMAJA DI PERKOTAAN - Nabila Inesta Dyaudi (2023)
Nutritional problems in adolescents have an impact on growth and development and affect the quality of life in the future. Overweight is generally caused by dietary habits, physical activity, and knowledge of balanced nutrition. In adolescents there are lifestyle changes, such as eating patterns that often consume fast food, sweet foods and drinks, and rarely consume vegetables and fruit and low physical activity caused by a lack of knowledge about a healthy lifestyle. This study aims to analyze the relationship between dietary habits, physical activity, and knowledge of balanced nutrition with the nutritional status of adolescents in urban areas. This study uses a cross sectional design with chi square. Respondents of this study were high school students in East Jakarta City as many as 93 respondents using quota sampling method. The research data were obtained from food frequency questionnaire (FFQ), physical activity level (PAL), and a balanced nutrition knowledge questionnaire. The results showed that there was a significant relationship between eating patterns of consumption of fast food and fried foods (p = 0,016), dietary patterns of consuming sweet foods and drinks (p = 0,016), and physical activity weekdays (p = 0.002) and weekends (p = 0,043) on nutritional status in adolescents in urban areas. However, vegetable consumption patterns (p = 0.075), fruit consumption patterns (p = 0.619), and knowledge of balanced nutrition (p = 1,000) had no relationship with the nutritional status of adolescents in urban areas. Therefore, our study condlude that consumption of fast food and fried foods, consumption of sweet foods and beverages, as well as physical activity are strongly associated withnutritional status in adolescents.